Trigger Levels on Transport Mode Choice by Using Graphical Analysis - Nur Fahriza, M. A.; A., Zulkiple (Penerbit Universiti Malaysia Pahang, 2015)
This paper presents the evaluation of trigger levels at the equilibrium condition which the users’ preferred mode choice is equal for both private vehicles and public transport. The research is conducted at Klang where the local authority is planning to construct a new Park and Ride at the Klang Commuter’s Station. This study selected travel time as an important factor in triggering the users’ mode choice in either selecting public transport or private vehicles for their daily journey. Therefore, the trigger levels’ condition said the users’ in deciding their mode of transport, as users often seek for a faster and more convenient method of transportation in getting themselves to reach their destination, especially during morning peak hour. The data is collected by means of The Bus Route in this study. The trigger levels are evaluateduponanalyzing the data by using Graphical Analysis. The results show that almost equal of travel time was established between private and public transport. The outcome of this study may in turn be utilized to persuade users’ to change their mode choice from private to public transport.